2019
DOI: 10.1016/j.sopen.2019.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of body mass index on outcomes in patients undergoing surgery for diverticular disease

Abstract: Background We hypothesized that increasing body mass index is a risk factor for surgical complications in surgery for diverticulitis. We assessed the relationship of body mass index and surgical complications following surgery for diverticular disease. Methods We used National Surgical Quality Improvement Program database from 2005 to 2015. Patients undergoing surgery for diverticular disease during that period were included and stratified into 9 groups based on their b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(31 reference statements)
0
2
2
Order By: Relevance
“…Despite this notable increase in MO prevalence and the probable increase in the severity and complications of CDD, we noted a decline in mortality and LOS over the study period. These improvements in overall outcomes are contrary to the findings of other retrospective reviews [30,31] that showed that patients with higher visceral/subcutaneous fat ratios and increasing body mass index were more likely to require emergency surgery, have longer hospital stays, and develop more complications, including superficial surgical site infection, deep incisional surgical site infection, organ space surgical site infection, wound disruption complications, ventilator dependence > 48 hours, acute renal failure, and return to the operating room. Neither study, however, demonstrated worse mortality outcomes.…”
Section: Discussioncontrasting
confidence: 92%
“…Despite this notable increase in MO prevalence and the probable increase in the severity and complications of CDD, we noted a decline in mortality and LOS over the study period. These improvements in overall outcomes are contrary to the findings of other retrospective reviews [30,31] that showed that patients with higher visceral/subcutaneous fat ratios and increasing body mass index were more likely to require emergency surgery, have longer hospital stays, and develop more complications, including superficial surgical site infection, deep incisional surgical site infection, organ space surgical site infection, wound disruption complications, ventilator dependence > 48 hours, acute renal failure, and return to the operating room. Neither study, however, demonstrated worse mortality outcomes.…”
Section: Discussioncontrasting
confidence: 92%
“…31 Additional research employing more substantial sample sizes may yield advantageous results in definitively ascertaining the influence of body mass index (BMI) on complications associated with wounds following transplantation. [32][33][34] In contrast to findings that have suggested genderspecific variations in surgical outcomes, the incidence of wound complications was not substantially impacted by the gender of the recipients. 35 Variations in surgical techniques, demographic distinctions, or holistic care approaches utilized by the participating centres could account for this disparity.…”
Section: Discussioncontrasting
confidence: 64%
“…Based on our analysis, it appears that an elevated body mass index (BMI) might be correlated with an increased likelihood of postoperative complications; however, this finding did not attain the usual thresholds of statistical significance 31 . Additional research employing more substantial sample sizes may yield advantageous results in definitively ascertaining the influence of body mass index (BMI) on complications associated with wounds following transplantation 32–34 …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation